2022
DOI: 10.3389/fphys.2021.767445
|View full text |Cite
|
Sign up to set email alerts
|

Triceps Surae Muscle-Tendon Properties as Determinants of the Metabolic Cost in Trained Long-Distance Runners

Abstract: Purpose: This study aimed to determine whether triceps surae’s muscle architecture and Achilles tendon parameters are related to running metabolic cost (C) in trained long-distance runners.Methods: Seventeen trained male recreational long-distance runners (mean age = 34 years) participated in this study. C was measured during submaximal steady-state running (5 min) at 12 and 16 km h–1 on a treadmill. Ultrasound was used to determine the gastrocnemius medialis (GM), gastrocnemius lateralis (GL), and soleus (SO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…These findings suggest that changes in tissue stiffness induced by acute heat exposure are transient and do not translate into chronic adaptations after repeated active HA sessions. Unaffected muscle and tendon stiffness suggest no effect on the metabolic cost, at least linked to soft tissue stiffness (48), reinforcing the nonalteration of muscle–tendon unit interactions and their absence of negative effect on performance after active HA.…”
Section: Discussionmentioning
confidence: 96%
“…These findings suggest that changes in tissue stiffness induced by acute heat exposure are transient and do not translate into chronic adaptations after repeated active HA sessions. Unaffected muscle and tendon stiffness suggest no effect on the metabolic cost, at least linked to soft tissue stiffness (48), reinforcing the nonalteration of muscle–tendon unit interactions and their absence of negative effect on performance after active HA.…”
Section: Discussionmentioning
confidence: 96%
“…For one, the Achilles tendon is expected to experience greater biomechanical loads than the tibialis cranialis tendon. The triceps surae-Achilles tendon unit provides body weight support against gravity and propels the body during locomotion (Machado et al, 2021); conversely, the tibialis cranialis muscle-tendon unit contributes to foot motion during the swing phase of locomotion (Viidik, 1969). In vivo motion of the artificial tendon and suture relative to the anchor, which could affect wear of the suture against the anchor eyelet, could have been greater for the Achilles tendon than for the tibialis cranialis tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive submaximal voluntary contractions of triceps surae account for 25% to 40% of the whole‐body energy expenditure during long‐distance running 4,5 . The MTU behavior (including length, contraction/lengthening length, and velocity) and dynamics (force and power) are considered determinant factors of force production, muscle metabolic cost, and running economy in long‐distance runners 6,7 . Swinnen et al 8 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The MTU behavior (including length, contraction/lengthening length, and velocity) and dynamics (force and power) are considered determinant factors of force production, muscle metabolic cost, and running economy in long-distance runners. 6,7 Swinnen et al 8 preliminarily showed that the medial gastrocnemius (MG) fascicle contraction length and velocity were lower during the running stance phase in habitual non-RFS runners than in RFS runners. Our previous studies reported the MG in habitual non-RFS runners seemed to contract with greater force in relatively isometric behavior and at a slower shortening velocity than RFS during running.…”
Section: Introductionmentioning
confidence: 99%